2021
DOI: 10.1007/s00296-021-04875-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of antiphospholipid antibodies in patients with coronavirus disease 2019 admitted to intensive care units: a prospective observational study

Abstract: Coronavirus disease 2019 (COVID-19) increases the risk of coagulopathy. Although the presence of antiphospholipid antibodies (aPLs) has been proposed as a possible mechanism of COVID-19-induced coagulopathy, its clinical significance remains uncertain. Therefore, this study aimed to evaluate the prevalence and clinical significance of aPLs among critically ill patients with COVID-19. This prospective observational study included 60 patients with COVID-19 admitted to intensive care units (ICU). The study outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Yet during COVID-19, some authors have suggested a pathological role to aPL to explain high number of thrombotic events. However some authors did not show any relationship of aPL and thromboses [ 18 , 54 , 55 ]. Differences of aPL prevalence could be observed in all types of aPL studied.…”
Section: Discussionmentioning
confidence: 99%
“…Yet during COVID-19, some authors have suggested a pathological role to aPL to explain high number of thrombotic events. However some authors did not show any relationship of aPL and thromboses [ 18 , 54 , 55 ]. Differences of aPL prevalence could be observed in all types of aPL studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the LA test is functional assay, being influenced by multiple factors and should be interpreted with caution. The presence of aCL IgG is reported in 0–48%, and aCL IgM 0–21% ( 1 , 17 ). Anti-β2-GPI antibodies are less frequent, with anti-β2-GPI IgM reported in 0–16%, and anti-β2-GPI IgG in 2–18.2% ( 17 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…A review of these studies, however, nevertheless lends itself to several key observations. Some have found no consistent association of antiphospholipid antibodies and thrombosis or disease severity [46,49,51,53,64,69,71]. Whether detected at the time of first patient presentation or shortly thereafter, such antibody status is time-accrued, maximizes in over 1 month after infection onset, and tends to be transient [49,68,70].…”
Section: Antiphospholipid Antibodies and Covid-19 Infectionmentioning
confidence: 99%